Particle detectors as witnesses for quantum gravity - Faure, Remi; Perche, T. Rick [UNESP]; Torres, Bruno de S. L. [UNESP] (Amer Physical Soc, 2020)
We present a model for the coupling of nonrelativistic quantum systems with a linearized gravitational field from a Lagrangian formulation. The coupling strongly resembles the light-matter interaction models that are known to be well approximated by the Unruh-DeWitt detector model for interactions with quantum fields. We then apply our model to linearized quantum gravity, which allows us to propose a detector based setup that can in principle probe the quantum nature of the gravitational field.